Furin cleavage is not a requirement for Drosophila Notch function. - Kidd, S.; Lieber, T. (Mechanisms of Development, 2002)
Notch (N) is a large transmembrane protein that acts as a receptor in an evolutionarily conserved intercellular signalling pathway. Because of this conservation, it has been assumed that biochemical events mediating N function are identical in all species. For instance, intracellular maturation by furin protease and subunit assembly leading to the formation of a heterodimeric cell surface N receptor are thought to be central to its function in both mammals and flies. However, in Drosophila the majority of N appears to be full-length. It has not been determined whether this full-length N protein is on the cell surface. We describe experiments which indicate that unlike mammalian N, the majority of Drosophila N on the cell surface is full-length and that in Drosophila, in vivo, furin cleavage is not required for biological activity. We further show that the behaviour of fly and mouse N can be interchanged simply by swapping the regions in which the mammalian furin-like cleavage site is located.